CONTEMPORARY DEVELOPMENT TENDENCIES OF HIGHER EDUCATION IN FRANCE - Durdas, Alla (The Modern Higher Education Review, 2018)
The contemporary tendencies in the development of higher education of France in the context of integration processes have been considered in the article. The peculiarities of the implementation of the main provisions of the Bologna Convention by the French higher school have been traced. The innovations inherent to the modern higher education of France and its desire to preserve the centuries-old national achievements have been highlighted.